Preface for the special issue of Mathematical Biosciences and Engineering, BIOCOMP 2012 - Aniello Buonocore; Antonio Di Crescenzo; Alan Hastings (Mathematical Biosciences and Engineering)
The International Conference ``BIOCOMP2012 - Mathematical Modeling and Computational Topics in Biosciences'',was held in Vietri sul Mare (Italy), June 4-8, 2012. It was dedicated to the Memory of Professor Luigi M. Ricciardi(1942-2011), who was a visionary and tireless promoter of the 3 previous editions of the BIOCOMP conference series.We thought that the best way to honor his memory was to continue the BIOCOMP program. Over the years, thisconference promoted scientific activities related to his wide interests and scientific expertise, which ranged invarious areas of applications of mathematics, probability and statistics to biosciences and cybernetics, alsowith emphasis on computational problems. We are pleased that many of his friends and colleagues, as well asmany other scientists, were attracted by the goals of this recent event and offered to contribute to its success.For more information please click the “Full Text” above.